Association between migraine and cardiovascular disease: A cross-sectional study - Wang, Kai; Mao, Yukang; Lu, Miao; Ding, Yinzhang; Li, Zhongming; Li, Yansong; Liu, Xianling; Sun, Yan; Hong, Jian; Xu, Di; Wu, Tingting (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiovascular disease (CVD) poses a tremendous threat to global health, giving rise to exceedingly high morbidity and mortality among patients. A migraine is a common neurological disorder characterized by recurrent attacks of severe headache, while its cardiovascular burden remains unclear. Therefore, this study aims to investigate whether migraine is associated with CVD. Methods: The cross-sectional data of 5,692 subjects aged 20 or above was obtained from the National Health and Nutrition Examination Survey (NHANES) 1999–2004. To determine whether migraine is associated with CVD, weighted logistic regression models were used. In a subsequent subgroup analysis, several confounding factors were also explored to investigate the association between migraine and CVD. Results: In total, 5,692 subjects were enrolled in this study, with the prevalence of CVD being 13.3%. Participants with CVD tended to be older, male, non-Hispanic whites, more educated, former smokers, and alcohol drinkers, and had a higher waist circumference, less physical activity, a higher level of triglyceride and creatinine as well as a lower level of high-density lipoprotein cholesterol (HDL-C) and estimated glomerular filtration rate (eGFR) (all P < 0.05). Considering all potential confounders, migraine was associated with a higher risk of CVD [odds ratios (ORs) 2.77; 95% confidence intervals (CIs): 1.56–4.90]. Subgroup analysis showed a higher risk of CVD in females, those older than 60 years, with a lower body mass index (BMI) level (≤ 30 kg/m2), a higher level of eGFR (> 90 mL/min/1.73 m2), hypertension and hyperlipidemia and without diabetes. Conclusions: In summary, our study revealed a positive association between migraine with CVD in a nationally representative US adult population. Our findings highlighted that migraine should be considered an important risk factor for CVD.